Kidney disease and hemodialysis: identification of blood biomarkers to detect heart failure and kidney failure - Barbara Letícia Dudel Mayer; Pollyana Thays Lameira da Costa; Maria Elena Echevarría-Guanilo; Silvana Silveira Kempfer; Kleber Maciel da Silva Pieri (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2020)
Introduction: Chronic hemodialysis aims to replace renal function and provides an extension of life expectancy, however, complications do occur and they can be serious even fatal. Knowing the complications can enable a better prognostic evaluation and use of an intervention approach. These can be identified when performing anamnesis and physical examination, as well as, with greater precision, by means of renal and cardiac biomarkers and imaging tests. Objectives: to identify valid blood biomarkers to detect heart failure and kidney failure associated with kidney disease and hemodialysis. Methods: systematic literature review conducted in August 2018 in the following: Web Of Science, PubMed, Scopus, Cinahal, Cochrane, Science Direct and Lilacs. The guiding question was: "What are the blood biomarkers used to detect heart failure and kidney failure?" A total of 537 publications were found, 94 of these appeared more than once, 383 were excluded after reading titles and abstracts, 32 were excluded after reading the full texts, and 10 were excluded in the quantitative and qualitative synthesis. Results: 18 papers compose the final sample and report laboratory and imaging tests, instruments to assess the risk of kidney and heart failure, and also clinical management of the progression of kidney and heart failure. All the studies correlated risk of mortality and death outcome. Conclusion: laboratory tests are important to identifying kidney and heart failure and need to be used to improve clinical management of the hemodialysis treatment of people with chronic kidney disease in order to improve quality of life and life expectancy.